Asymptomatic infection and unrecognised Ebola virus disease in Ebola-affected households in Sierra Leone: a cross-sectional study using a new non-invasive assay for antibodies to Ebola virus. Issue 6 (June 2017) - Glynn, Judith R; Bower, Hilary; Johnson, Sembia; Houlihan, Catherine F; Montesano, Carla; Scott, Janet T; Semple, Malcolm G; Bangura, Mohammed S; Kamara, Alie Joshua; Kamara, Osman; Mansaray, Saidu H; Sesay, Daniel; et al.
Summary: Background: The frequency of asymptomatic infection with Ebola virus is unclear: previous estimates vary and there is no standard test. Asymptomatic infection with Ebola virus could contribute to population immunity, reducing spread. If people with asymptomatic infection are infectious it could explain re-emergences of Ebola virus disease (EVD) without known contact. Methods: We validated a new oral fluid anti-glycoprotein IgG capture assay among survivors from Kerry Town Ebola Treatment Centre and controls from communities unaffected by EVD in Sierra Leone. We then assessed the seroprevalence of antibodies to Ebola virus in a cross-sectional study of household contacts of the survivors. All household members were interviewed. Two reactive tests were required for a positive result, with a third test to resolve any discrepancies. Findings: The assay had a specificity of 100% (95% CI 98·9–100; 339 of 339 controls tested negative) and sensitivity of 95·9% (89·8–98·9; 93 of 97 PCR-confirmed survivors tested positive). Of household contacts not diagnosed with EVD, 47·6% (229 of 481) had high level exposure (direct contact with a corpse, body fluids, or a case with diarrhoea, vomiting, or bleeding). Among the contacts, 12·0% (95% CI 6·1–20·4; 11 of 92) with symptoms at the time other household members had EVD, and 2·6% (1·2–4·7; 10 of 388) with no symptoms tested positive. Among asymptomatic contacts, seropositivity was weakly correlated with exposure level. Interpretation: This new highly specific and sensitive assay showed asymptomatic infection with Ebola virus was uncommon despite high exposure. The low prevalence suggests asymptomatic infection contributes little to herd immunity in Ebola, and even if infectious, would account for few transmissions. Funding: Wellcome Trust ERAES Programme, Save the Children.